Telferia Occidentalis and Vitamin C Attenuate Phenylhydrazine-Induced Haemolytic Anaemia and Associated Cardio-renal Dysfunctions via Inhibition of Oxidative Stress and Proapoptotic -Protein (Bax) Expressions - Ajibade, Temitayo Olabisi; Oyagbemi, Ademola Adetokunbo; Omobowale, Temidayo Olutayo; Asenuga, Ebunoluwa Rachael; Saba, Adebowale Bernard (Drug Research, 2018)
Background The study investigated the modulatory roles of the aqueous leaf extract of Telferia occidentalis, a traditional haematinic, and vitamin C on cardiovascular dysfunction associated with subchronic Phenylhydrazine exposure.Methods Fifty adult male rats were randomly selected and divided into one of five groups of ten animals each: Control; 40 mgkg−1 Phenylhydrazine (PHZ); PHZ with 100 mgkg−1 T.occidentalis; PHZ with 200 mgkg−1 T.occidentalis; and PHZ with 100 mgkg−1 vitamin C.Results Oral exposure of rats to PHZ, without T. occidentalis or vitamin C treatment, resulted in a significant (p<0.05) decrease in the haematological parameters, but increased the blood pressure parameters of rats However, treatment with vitamin C and T. occidentalis leaf extract significantly (p<0.05) ameliorated the aforementioned PHZ-induced alterations of rats haemogram, and blood pressure. Biochemical analysis revealed significant (p<0.05) reduction in the activities of superoxide dismutase and catalase of untreated PHZ-exposed rats, but the levels of malondialdehyde, hydrogen peroxide and myeloperoxidase of the rats were significantly (p<0.05) increased compared with those of the extract treated rats. Immunohistochemical analysis revealed a greater expression of Bax-protein in the cardiac and renal tissues of the untreated PHZ exposed rats, compared with the extract and vitamin C treated groups.Conclusions The mitigation of oxidative stress and inhibition of Bax-protein expression are probable mechanisms of action of T. occidentalis in the amelioration of haemolytic anaemia, and its use as adjunct medication in the management of some diseases is justifiable
Keywords: anaemia; apoptosis; antioxidant; chemoprevention